Strengthening the links between mapping, planning and global engagement for disease elimination: lessons learnt from trachoma. Issue 10 (15th June 2018) - Courtright, Paul; Rotondo, Lisa A; MacArthur, Chad; Jones, Iain; Weaver, Angela; Negash, Biruck Kebede; Olobio, Nicholas; Binnawi, Kamal; Bush, Simon; Abdala, Mariamo; Haddad, Danny; Bonfield, Astrid; et al.
Abstract : Background: Trachoma is the leading infectious cause of blindness. Until recently, reliable data on the global extent of the disease, detailed plans for elimination, and government, donor and partner engagement were all inadequate. Methods: The trachoma community undertook a systematic, three-pronged strategy to map trachoma district by district, develop national-level trachoma elimination plans, and create a framework for governments, donors and partners to convene and coordinate in support of trachoma elimination. Result: There has been a frame-shift in internal and external perceptions of the global trachoma programme, from being an effort working towards disease control in focussed geographical areas, to one in the process of achieving worldwide disease elimination. Multiple factors contributed to the successful implementation of mapping, planning, and cross-sectional engagement of governments, partners and donors. Conclusions: Elimination of trachoma is possible if the right combination of factors is in place. Planning for success is a critical first step. Some remaining challenges must still be addressed if the elimination targets are to be successfully attained.